1996
DOI: 10.1007/bf01237879
|View full text |Cite
|
Sign up to set email alerts
|

Density-dependent natural selection inDrosophila: Trade-offs between larval food acquisition and utilization

Abstract: Natural selection at high densities has often been postulated to favour the evolution of greater efficiency of food use. Contrary to this expectation, a previous study suggested the existence of a trade-off between larval feeding rate and efficiency at using food to complete larval development in populations of Drosophila melanogaster subjected to crowding for many generations. In this paper, we confirm the generality of such a density-dependent trade-off between food acquisition and utilization by demonstrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
160
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(166 citation statements)
references
References 32 publications
5
160
1
Order By: Relevance
“…However, a subsequent experiment whereby only the larval stage was subjected to high or low densities explicitly demonstrated that resource availability can influence resultant trait evolution. Examination of trait expression across multiple ration levels revealed significant interactions between food level and selected line for larval survivorship because the high-density larval lines had lower survival only at low levels of food availability (27). Similar interactions between selection regime and food treatment were also observed in Drosophila lines that were selected for increased and decreased weight at ecolsion under two contrasting food levels (28,29).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, a subsequent experiment whereby only the larval stage was subjected to high or low densities explicitly demonstrated that resource availability can influence resultant trait evolution. Examination of trait expression across multiple ration levels revealed significant interactions between food level and selected line for larval survivorship because the high-density larval lines had lower survival only at low levels of food availability (27). Similar interactions between selection regime and food treatment were also observed in Drosophila lines that were selected for increased and decreased weight at ecolsion under two contrasting food levels (28,29).…”
Section: Discussionmentioning
confidence: 60%
“…The results of Drosophila selection experiments provide a clear example of the selective influence of population density and resource availability on the evolution of general life history strategies (22)(23)(24)(25)(26)(27)(28)(29). Mueller et al (22)(23)(24)(25) reared populations of Drosophila at high or low densities and evaluated the evolution of population growth rates, which is a composite of the life history traits considered in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that variation of diet composition leads to selection pressure on larval survival. Joshi and Mueller (1996) indicated that food requirements for successful pupation may well be an accurate reflection of food requirements for the completion of development to the adult stage. Sisodia and Singh (2012) found that flies developed under protein-rich conditions had reduced egg-to-adult viability.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, higher larval feeding rates and a greater tolerance to ammonia, which is genetically correlated with urea tolerance (Borash, Pierce et al 2000), appear to be characteristic adaptations to larval crowding in D. melanogaster . The lower minimum food requirement of the fast populations is evidently insufficient to offset the reduction in competitive ability owing to lower larval feeding rate and urea tolerance, supporting the notion that, at least in organisms showing primarily scramble competition, the efficiency of food acquisition may be a far more important determinant of competitive ability than the efficiency of conversion of food to biomass (Joshi & Mueller 1996). Overall, our results suggest that, the among-species correlation between fast development and competitive ability notwithstanding, microevolutionary reductions in development time are unlikely to result in the correlated evolution of enhanced competitive ability in Drosophila species.…”
Section: Discussionmentioning
confidence: 64%
“…Most importantly, the fast populations have evolved lower larval feeding rates and urea tolerance than controls, apparently as part of a syndrome of reduced energy expenditure Prasad et al 2001). Higher larval feeding rates are a strong correlate of competitive ability in D. melanogaster, owing to the necessity of ingesting sufficient food to sustain development before it runs out in a crowded culture (Joshi & Mueller 1996). In crowded cultures, levels of nitrogenous waste (especially ammonia) also rapidly build up to toxic levels (Borash et al 1998).…”
Section: Discussionmentioning
confidence: 99%